Sistem Informasi Manajemen Persediaan Dan Pendistribusian Barang Hotel Nite & Day Laguna Bintan - Tanjungpinang - Leva Affrillianggi Falihah; Larasati Indriastuti; Oktavianto (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2018)
To accelerate company operation, a company must able to manage the stock, need to know the in and out of the stock they have. The bigger the company the more difficult for the store keeper to record all data. So of course the company need a information technology that help the operation of the company, that intend to ensure accuracy of the right data and the right time. Inventory and Distribution Management Information System is a way to expected to help in processing of the stock data. This application is build using the waterfall method. This type of method consists of 6 stages, namely planning, analysis, design, implementation, testing and maintenance. This information system also uses the Java Netbeans IDE and MySQL database to build the stock management application. The results of this information system indicate that this can be used in assisting the work of the warehouse in processing the goods data in the related company. So that it can help effectiveness in its work